The Silent Revolution: Education and Instability in the Gulf Monarchies - Bahgat, Gawdat (Tufts Archival Research Center, 2005)
Volume 22, Issue 1. Winter/Spring The six Gulf monarchies need to reform their education systems to achieve coherence between their educational goals and their socioeconomic needs.